Comparative study between posturography and caloric test in balance disorders - Swami, Himanshu; Sivan, Maneesha; M., Bharath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Vertigo is a common clinical problem encountered by otolaryngologist. There are various causes balance disorders including pathologies of inner ear, somatosensory system and visual disturbances to name a few. Caloric test is suitable for inner ear disorders. Posturography promises to be more holistic in diagnosis of balance disorders. Methods: 50 patients suffering from imbalance were accrued. They were subjected to caloric test and posturography by using static balance platform. Canal paresis and directional preponderance were measured by caloric test and modified clinical test for sensory interaction on balance (mCTSIB was performed on static balance platform). Results: Caloric test was found to be positive in 17 whereas static balance platform detected abnormalities in 28 patients. Conclusions: Posturography by use of static balance platform can be an important tool in determining the cause of imbalance. The detection of abnormalities as compared to caloric test is statistically significant.